Songbirds phonics : level 5 : no milk today - Tree, Oxford Reading ([S.l.] : Oxford University Press, 2012)
How can Mrs Green feed her cat in No Milk Today? Level 5 Songbirds Phonics books focus on different spelling patterns for the long vowel sounds oo as in moon, oo as in good, ow as in down, oi as in coin and soft c as in dice. The focus phonics in this book are oo as in moon, oo as in good, ow as in down and oi as in coin. Oxford Reading Tree Songbirds Phonics are highly decodable, beautifully illustrated stories written by best-selling author Julia Donaldson. The series contains a variety of storylines, rhyme, rhythm and genre ensuring there is something for every child to enjoy. The rich, patterned language in the stories is decodable making them perfect for children to practise their phonics. Songbirds Phonics can be used as a complete phonics programme, or the individual books can be used for phonics practice alongside any other phonics programme. Each book contains inside cover notes to support parents/carers with their children's phonics practice and comprehension.